Integrated approach of anatomical, physiological and biochemical parameters for the study of tolerance mechanisms to cadmium in tomato accessions - Carvalho, Marcia Eugenia Amaral de (2017)
Tomato (Solanum lycopersicum L.) consumption has increased every year due to the fruit attractiveness, several utilizations, and beneficial effects for human health. However, tomato fruits can accumulate a Cd concentration that exceeds the safety threshold for human consumption of vegetables, even when plants are grown in soil with acceptable Cd level. Cd is a non-essential, hazardous element to biological systems, triggering several diseases in humans. In plants, Cd disturbs the antioxidant machinery, changes the nutritional status, and impairs the photoassimilate production and/or partitioning, hence reducing fruit yield and quality. However, distinct tomato accessions can present contrasting tolerance degree to Cd toxicity, as detected by our group in previous studies. The use of these accessions is a powerful approach to identify strategies employed by plants to cope with Cdinduced challenges, and the acknowledgement of such strategies can be potentially used in breeding and biotechnological programs to improve fruit yield and quality in crops that were cultivated in contaminated fields. The set of studies that compose the present thesis aimed (i) to identify the main mechanisms for the contrasting tolerance degree to Cd-induced toxicity in tomato accessions after short and long-term Cd exposure; (ii) to evaluate the relationship among tolerance degree and fruits attributes in plants that were grown in Cd-containing soil, and (iii) to determine the transgenerational effects of Cd-induced stress. In the first experiment, nine tomato accessions with a varied tolerance degree, which was based on biomass accumulation, to Cd exposure were grown in hydroponic solution containing CdCl2 35 μM for 6 days. Avoidance of high Mg concentration in roots was identified as a plant strategy to mitigate Cd toxicity by preventing formation of root hairs. Regarding the mode of action of Cd toxicity, Mn excess in leaves, in addition to the high Cd concentration per se, seems to be coupled to leaf damages that are enhanced by the increased Zn and B concentrations in the photosynthetic tissues. In the second experiment, tolerant (Yoshimatsu) and sensitive (Tropic Two Orders) genotypes were grown in Cd-containing soil, in order to evaluated production parameters. After plant exposure to Cd, the tolerant genotype presented an increased fruit diameter, height and weight, when compared to the control plants. In both cultivars, Cd concentration varied according to the following descending order: roots = leaf blade > (floral receptacle, peduncle and sepals) > stem = fruit peel = fruit pulp. Moreover, data suggested that floral receptacle and its related-structures acted as a barrier to the Cd transportation to the fruits, but it was not enough to avoid Cd reaching the fruits. Furthermore, Cd exposure provoked remarkable reductions in the Mg concentration in roots of sensitive and tolerant genotypes, revealing that both tomato cultivars are able to employ this mechanism for plant acclimation to long-term Cd exposure. Considering such information, it is possible that, under the short-term Cd exposure, tolerant accessions activate this mechanism either early or faster than sensitive genotypes. In addition, positive transgenerational effects on seed germination and vigor of the tolerant genotype were triggered by the plant-mother cultivation in Cd-containing media, despite of the increased chromosomal abnormality. This work reported new insights about the effects of Cd exposure on tomato development, tolerance mechanisms, fruit quality and yield of tomato, as well as Cd distribution in the plants.